The Effect of beating degree on physical characteristics of wood pulp fibres - Potůček, František; Marhanová, Milena (Univerzita Pardubice, 1999)
The purpose of our investigation was to study the influence of the degree of beating on the physical characteristics of unbleached and bleached kraft pulp fibres. For various degrees of beating, the specific volume as well as specific surface basedon on both volume and mass of fibres were determined. To characterize pulp fibres at different degrees of beating, the weighted and arithmetic average lengths of fibres were measured.
Keywords: buničina; mletí; vlákna